Effect of Steering Gear Parameters of Crawler Tractor Cornering Ability (Agricultural Engineering, 2016)
Crawler tractor with specific loads on the hitch loses traction abilities during cornering and causes intensive destruction of the surface layer of soil. This phenomenon may be limited if relevantly selected parameters of the cornering mechanisms were applied. The objective of the paper was to determine the impact of the cornering mechanism parameters on the crawler tractor maneuver ability. The object of the research was a planetary cornering mechanism which enables fluent change of the cornering radius through the change of the rotational speed of planetary gears drive by pneumatic engines. Relations of the turning radius to the slip of the spinning and overleaping crawler at the speed of 7 km·h-1 without the load on the hitch and with the load of 40 kN were defined. The average values of drift and the turning radius as a function of drive speed from 0 to 2.5 m·s-1 on the moist soil μ=0.4 and dry soil μ=0.8 were determined. Relations of the turning radius to the pressure of oil pump oil, to the drive speed and to the load on the hitch were set forth. The research proved that when using the hydraulic pump with the regulated expense the working pressure of oil may be maximally reduced to 30 MPa, the power of the pump may be reduced by twofold, the possibility of turning in difficult field conditions within the scope of the required speed may be enabled. To ensure the required turning radius of the crawler tractor it is recommended to install the pump with the efficiency of 33 cm3·rot-1 and a regulated hydraulic motor with the capacity of 56 cm3·rot-1 with a power regulation within 2.0-2.5, at the same time maximum pressure of liquid will not exceed 35 MPa and the determined power of the hydraulic gear will amount to 52.6 kW.